Atrial functional mitral regurgitation: mechanisms and surgical implications. (September 2020) - Fan, Yiting; Wan, Song; Wong, Randolph Hung-Leung; Lee, Alex Pui-Wai
The term atrial functional mitral regurgitation refers to a newly recognized disease entity in which mitral regurgitation occurs secondary to left atrial disease, without left ventricular dilatation and intrinsic mitral valve disease, typically in the setting of long-standing atrial fibrillation. Recent evidence suggests that atrial functional mitral regurgitation is associated with increased risk of death and heart failure re-hospitalization. The etiology, pathophysiology, and mechanism of atrial functional mitral regurgitation is not completely understood but they should not be regarded as the same as for the conventional type of functional mitral regurgitation secondary to left ventricular dilatation and dysfunction. Mitral annular dilatation, atriogenic leaflet distortion, insufficient leaflet remodeling, and subtle left ventricular dysfunction may play a role in the pathogenesis of atrial functional mitral regurgitation. The therapeutic and surgical considerations of atrial functional mitral regurgitation are different from those of ventricular functional mitral regurgitation. In this review, we assess current evidence regarding this new disease entity and propose a new surgical approach based on up-to-date understanding and experience of this condition.